Orewoet's Journey: The Reuse of a Medieval Mystical Term in a Contemporary Novel - Fraeters, Veerle (Studies in spirituality, 2025)
After centuries of oblivion, the Middle Dutch neologism orewoet [madness of love] – a key term in the writings of the medieval mystic Hadewijch of Brabant (c. 1240) – has made a striking comeback in the contemporary cultural field of the Low Countries. This article situates the resurrection of orewoet in the broader context of the religious turn of the twenty-first century and the ‘affective dominant’ evident in contemporary literature, taking the novel Orewoet (2016) by Dutch author Emy Koopman as a case study. Using the methodology of Cultural Transfer Studies, we analyze the semantic field of maddening desire in, first, Hadewijch’s mystical love lyrics, and second, Koopman’s novel. This comparative analysis reveals that, in the secular love story Orewoet, only one aspect of Hadewijch’s orewoet is appropriated: the lover’s suffering from unrequited love as a destructive force. The deifying potential of orewoet as a painful yet transformative force for self-annihilation that propels the lover into spiritual maturity, did not survive its journey from Hadewijch to Koopman.